Natural resource curse : The case of Russia - Belyakova, Elena (2017)
The purpose of this paper is to provide insight into the problem of the natural resource curse, particularly in the Russian Federation, with respect to history, changes in oil prices and the situation in the world arena. With the hypothesis that the changes in oil prices affect the Russian GDP and the development of other non-oil based industries, two different regressions for two time periods are run. The results of the regressions and subsequent test confirm the hypothesis that Russian GDP depends on the oil prices and on changes on the world resource market. It is found, that in the Soviet period there was no dependence of Soviet economy on oil export and prices. The results are in support of the previous paper, written by Benedictow et al. (2010), that indeed Russian economy suffers from the natural resource curse.